PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR FOOD & BEVERAGE DI BURSA EFEK INDONESIA TAHUN 2019 - 2023) - Laila, Feby; Rosyati, Tati (Jurnal Nusa Akuntansi, 2025)
This study aims to analyze the effect of capital structure, company size and capital intensity on tax avoidance. This study was conducted by analyzing the financial statements of companies in food & beverage listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sampling technique in this study used the purposive sampling method, so that a research sample of 22 food & beverage companies listed on the Indonesia Stock Exchange in 2019-2023 was obtained. This study uses panel data regression analysis and hypothesis testing with a significance level of 5%. The test tool used is e-views software version 12 Student Version Lite. Based on the results of the hypothesis test, the results show that capital structure, company size and capital intensity simultaneously have a significant effect on tax avoidance. Partially, only the company size and capital intensity variables have a significant effect on tax avoidance, while the capital structure does not show a significant effect on tax avoidance, this finding provides insight that company size and capital intensity have a greater effect on tax avoidance compared to capital structure.